Pengembangan Media Pembelajaran Lampu Lava - Putri, Heti Hertika; Nurwita, Syisva; Margaretha, Lydia (Early Childhood Research and Practice, 2024)
This research aims to: (1) produce lava lamp media that are feasible as learning media. (2) knowing the teacher's response to the lava lamp media as a learning media at PAUD INTAN KASIH BUNDA Kec. Seluma this development uses the ADDIE development model. The data collection instrument in this study is a media expert validation questionnaire, material expert validation, and teacher response questionnaire. The subjects of this study consisted of 2 teachers at INTAN KASIH BUNDA early childhood education center in Seluma and 1 lecturer at Dehasen University. The data analysis technique used in this research is quantitative data analysis. The results of the study showed that in the first stage of material validation by material experts obtained 90% results and the second stage was declared feasible to use without revision with a percentage of feasibility of 100%. Then the data from the validation of media experts obtained a percentage score of 90.7% and the second validation stage obtained a score of 97.9% with a very good category and was declared suitable for use without revision. Lava lamp media is declared practical with a percentage of practicality of 95% based on data from the results of practicality by the teacher's response at INTAN KASIH BUNDA PAUD Kec. Seluma using a questionnaire. Therefore it can be concluded that the lava lamp learning media produced is feasible and practical as a learning media in the INTAN KASIH BUNDA Early Childhood Center, Seluma Subdistrict.